The triglyceride–glucose index is associated with no-reflow phenomenon in STEMI patients with type 2 diabetes after percutaneous coronary intervention - Ma, Juan; Wu, Peng; Ma, Shengzong; Ma, Xueping; Jin, Ping; Jia, Shaobin (Frontiers in Cardiovascular Medicine, 2024)
Background The relationship between the triglyceride–glucose (TyG) index and no-reflow phenomenon after percutaneous coronary intervention (PCI) in patients with type 2 diabetes mellitus (T2DM) and acute ST-segment elevation myocardial infarction (STEMI) remains unclear. This study aimed to investigate the relationship between baseline TyG index and no-reflow phenomenon in STEMI patients with T2DM after PCI. Methods This study enrolled 695 patients with T2DM and STEMI from the General Hospital of Ningxia Medical University (2014–2019). Patients were divided into tertiles according to the TyG index levels. The incidence of no-reflow phenomenon was recorded. A multivariate regression model was developed to analyze the association between the baseline TyG index and no-reflow phenomenon. The linear association between the baseline TyG index and no-reflow phenomenon was explored using smooth curve fitting with parallel subgroup analyses. Receiver operating characteristic (ROC) curves were generated to determine the predictive power of the TyG index. Results A multivariate logistic regression model revealed that the TyG index was an independent risk factor of no-reflow phenomenon [OR = 3.23, 95%CI: 2.15–4.86, P < 0.001], and the occurrence of no-reflow phenomenon increased gradually with the increase of TyG index tertile interval (P < 0.001). Smooth curve fitting showed that the TyG index was linearly related to the risk of no-reflow. Subgroup analysis showed that they participated in this positive correlation. The area under the ROC curve (AUC) of the TyG index for evaluating the occurrence of no-reflow was 0.710 (95% CI: 0.640–0.780; P < 0.01). Conclusions The TyG index is independently associated with no-reflow phenomenon, suggesting that the simple index of the TyG index can be used for risk assessment of no-reflow phenomenon after PCI in STEMI patients with T2DM.